Comparing the sensor glove and questionnaire as measures of computer anxiety - Nkalai, Tlholohelo Stephania (University of the Free State, 2014)
A vast amount of literature regarding computer anxiety exists. Consequently, a number of researchers have discovered different definitions for computer anxiety. Regardless of the numerous definitions, several researchers agree that computer anxiety involves emotional ‘fear’ or ‘apprehension’ when interacting or anticipating interaction with computers. Subsequently, some individuals who experience computer anxiety avoid using computers. This situation is undesirable because these days it is almost always a necessity for people to use computers in the workplace. It is therefore important to extensively investigate computer anxiety including measures which can be implemented to mitigate it. Different findings about computer anxiety regarding the correlates: gender, age, computer ownership, educational attainment and computer experience, exist. For example, while some research findings state that females experience higher levels of computer anxiety than males, other research findings assert that males experience computer anxiety more than the females. The contradictory findings regarding the correlates of computer anxiety could be attributed to the fact that most of the research studies which investigated computer anxiety relied solely on existing computer anxiety questionnaires. Using questionnaires exclusively poses various limitations which include relying on the ‘subjective’ responses of the participants. This research study incorporated another measurement of computer anxiety in addition to an existing computer anxiety questionnaire named Computer Anxiety Rating Scale. This additional measurement was performed using an instrument that measured physiological signals of a participant. The instrument is called an Emotion RECecognition system (EREC). It measures skin temperature and skin resistance and heart rate. Apart from the mentioned two, other data collection methods were used which are pre-test and post- test self-developed questionnaires, observations and interviews. With various measurements incorporated in this study, computer anxiety was investigated taking into consideration the following research questions:  To what extent does a sensor glove add value in measuring computer anxiety during usability testing when compared to anxiety questionnaires and observations?  To what extent is computer anxiety influenced by age, gender, computer experience, educational attainment, and ownership of a personal computer according to the anxiety questionnaire and the sensor glove? From the findings of the study in relation to the first research question, it can be concluded that the sensor glove does not add value. Instead, the sensor glove may add value when measuring stress. This means that although the EREC sensor glove measures skin conductance, changes in skin conductance may indicate changes in stress levels rather than anxiety levels. Regarding the second research question, it can be concluded that computer anxiety was not influenced by age, gender, computer experience, educational attainment, and ownership of a personal computer according to the anxiety questionnaire and the sensor glove.

Daar is ‘n geweldige groot hoeveelheid literatuur beskikbaar ten opsigte van rekenaarangstigheid. Gevolglik bestaan daar ‘n groot aantal verskillende definisies t.o.v. rekenaar-angstigheid. Ten spyte van die baie definisies, stem navorsers tog ooreen dat rekenaar-angstigheid emosionele vrees of vooropstelling insluit wanneer daar ‘n persoon met ‘n rekenaars werk, of selfs net daaraan dink dat hy met ‘n rekenaar moet werk. Die gevolg is dat sommige persone wat hieraan ly dit heeltemal vermy om met ‘n rekenaar te werk. Hierdie is nie die ideale toestand van sake nie aangesien dit bykans onmoontlik is om vandag sonder ‘n rekenaar in ‘n werkomgewing te funksioneer. Dit is daarom dit so belangrik is om deeglike navorsing te doen t.o.v. rekenaar-angstigheid, sowel as die maatreëls wat geïmplementeer kan word om dit aan te spreek. Verskillende gevolgtrekkings rakende die korrelate: geslag, ouderdom, besit van ‘n rekenaar, opvoedkundige vlak sowel as rekenaar-ervaring bestaan. Byvoorbeeld, sommige navorsingsresultate dui daarop dat die vroulike geslag hoër vlakke van rekenaar-angstigheid ervaar as hul manlike eweknieë, terwyl ander verslae weer die teenoorgestelde aandui. Hierdie teenstrydige resultate rakende die korrelate van rekenaar-angstigheid kan toegeskryf word aan die feit dat die meeste van die navorsingstudies wat hierdie fenomeen ondersoek, gebruik gemaak het van bestaande vraelyste. Deur slegs van vraelyste gebruik te maak plaas ‘n geweldige beperking op die navorsingsresultate daar slegs staat gemaak word op die “subjektiewe” terugvoer van die deelnemers. Hierdie navorsingstudie het, bo en behalwe die bestaande vraelyste, ook gebruik gemaak van ‘n alternatiewe metode om rekenaar-angstigheid te meet, naamlik die “Computer Anxiety Rating Scale”. Hierdie addisionele meting is gedoen deur gebruik te maak van ‘n instrument wat die fisiologiese tekens van ‘n deelnemer meet. Hierdie instrument staan bekend as die “Emotion RECognition system (EREC)”. Dit meet ‘n deelnemer se vel-temperatuur, vel-weerstand sowel as die tempo van sy hartklop. Afgesien van bogenoemde twee metodes, is daar ook gebruik gemaak van ander metodes om data te ersamel, bv. pre- en post-toets, self-ontwikkelde vraelyste, observasies en onderhoude. Opsomming Deur verskillende metodes te inkorporeer in hierdie navorsingstudie, is rekenaarangstigheid ondersoek ten opsigte van die volgende navorsigingsvrae: • Tot watter mate voeg die gebruik van ‘n sensor-handskoen waarde tot die meting van rekenaar-angstigheid tydens ‘n bruikbaarheidstudie in vergelyking met rekenaar-angstigheid vraelyste en observasies? • Tot watter mate word rekenaar-angstigheid beïnvloed deur ouderdom, geslag, rekenaar-ondervinding, opvoedkundige vlak en besit van ‘n persoonlike rekenaar na aanleiding van die angstigheid-vraelyste en die sensor-handskoen? Dit blyk uit die resultate van die studie, ten opsigte van die eerste vraag, dat die handskoen nie waarde toegevoeg het nie. Inteendeel, die sensor-handskoen kan eerder met sukses gebruik word om stresvlakke te meet. Dit beteken dat, alhoewel die EREC sensor-handskoen vel-weerstand meet, veranderinge in vel-weerstand ‘n verandering in stresvlakke kan aandui eerder as angstigheidsvlakke. Ten opsigte van die tweede vraag, kan dit aanvaar word dat rekenaar-angstigheid nie beïnvloed word deur ouderdom, geslag, rekenaar-ondervinding, opvoedkundige vlakke en besit van ‘n rekenaar nie, aldus die resultate van die angstigheid-vraelyste en die sensorhandskoen.
Dissertation (M.Sc. (Computer Science and Informatics))--University of the Free State, 2014
Keywords: Emotion recognition system; Computer anxiety; Emotion; Skin conductance; Physiological signals; Gender; Computer ownership; Educational attainment; Computer experience.; Human-computer interaction; Computers -- Psychological aspects; Computer literacy